Nomogram for predicting overall survival of metastatic pancreatic cancer patients based on HBV infection and inflammatory-nutritional biomarkers - Long, Xiawei; Li, Qian; Liao, Sina; Lin, Youzhi; Liao, Xiaoli (Frontiers in Oncology, 2024)
Purpose To develop and validate a nomogram for predicting the overall survival of patients with metastatic pancreatic cancer. Methods This retrospective study included 236 patients with metastatic pancreatic cancer treated at Guangxi Medical University Cancer Hospital between October 2013 and October 2022. Patients were grouped according to hepatitis B virus (HBV) infection status. Cox proportional hazard regression was used to identify the prognostic factors independently associated with overall survival. Results were used to build a nomogram, which was assessed through internal validation using bootstrap resampling. Results Patients in the HBV-positive group (N = 37) showed significantly better overall survival than those in the HBV-negative group (N=199; P = 0.014). Overall survival was independently associated with the following factors: HBV infection status, sex, chemotherapy, metastatic sites, a combined index of hemoglobin, albumin, lymphocytes, and platelets, neutrophil-albumin ratio, as well as levels of CA125. The nomogram showed good predictive power, with an area under the curve of 0.808 for the time-dependent receiver operating characteristic. Calibration and decision curve analyses indicated good calibration and clinical usefulness of the nomogram for predicting the overall survival of patients with metastatic pancreatic cancer. Conclusion A nomogram based on the HBV infection status and inflammatory nutritional markers may help predict the overall survival of patients with metastatic pancreatic cancer and guide personalized clinical treatment.